Awareness and satisfaction of mothers of under six children residing in the urban field practice area of Burdwan Medical College and Hospital regarding the services rendered by Anganwadi centers: a cross sectional study - Banerjee, Shibasish; Naskar, Somnath; Mitra, Kaushik; Nandi, Chinmay (International Journal Of Community Medicine And Public Health, 2018)
Background: Integrated child development services (ICDS) is the foremost symbol of India’s commitment to her children. The present study was done to assess the awareness of mothers of under six children residing in the urban field practice area regarding the services rendered by the Anganwadi Centres (AWC), to find out the satisfaction of mothers of under six children regarding quality of care received and to ascertain the availability of infrastructure and logistics of AWCs catering to the urban field practice area. Methods: A cross-sectional descriptive study was done at Alamganj, Purba Bardhaman, from October 2015 to December 2015 among mothers of under six children and AWCs located there. Mothers were interviewed, with the use of a predesigned and pretested schedule for assessing awareness and satisfaction of beneficiaries and predesigned, pretested check lists for infrastructure and logistics availability. The study was done after getting ethical approval. Data were analysed by SPSS 20. Results: Out of 3 AWCs 2 were pucca and 1 kutcha-pucca with poor sanitary facility. All the mothers were within 19-30 years age group. Immunization, nutrition and health education services were known to 98.2% mother. Only 57.1% and 48.2% mothers were aware of PSE and health check-up respectively. 73.3% mother preferred cooked food and rest raw food, 78.6% mothers were satisfied with amount of food and 71.4% were satisfied with quality. Bad taste and improper cooking were main reason behind non-acceptability. Conclusions: Findings of the study were better than earlier studies but still there were much scope for improvement in infrastructure, training and supervision.